Normative Juridical Analysis of the Decision South Jakarta District Court No. 508/pdt.p/2022/pn jkt.Sel About Interfaith Marriage - Mubarok, Andika (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Indonesia is a country with various religions that makes influence factors of pluralism. There are many diverse and recognized religions in Indonesia, so this has led to many different religious marriages being proposed in Indonesia. This article is about to discuss the normative juridical analysis of the South Jakarta District Court decision No. 508/Pdt.P/2022/PN JKT. The cell under review also uses an approach to Islamic law and positive law. The writing of this article uses a library research approach by examining journals, theses and other theses related to interfaith marriage. As for the results of this study, according to Islamic law (Al-Qur’an and Madhzab Ulama) interfaith marriage is permitted on condition that the woman is not a polytheist and is a woman of the Bible. According to Positive Law (KHI Article 40 & Article 44 and Law No. 1 of 1974 concerning Marriage Article 2 paragraph 1) it is explained that interfaith marriage is illegal and cannot be carried out by both Muslim men and non-Muslim women. Then according to the MUI Fatwa Number 4/MUNAS VII/MUI/8/2005 the law is haram with the consideration that interfaith marriages cause more mafsada than benefits